Educational technologies : enhancing the learning of scientific inquiry skills for bioscience students in Australian universities : final report. - Elliott, Kristine; Boin, Anna; Irving, Helen; Johnson, Elizabeth; Galea, Victor (Australian Learning and Teaching Council, 2010)
The changing nature of contemporary scientific practice means that broad employment opportunities exist for appropriately skilled bioscience graduates. The challenge for higher education in Australia is ensuring that students develop skills during their undergraduate studies such as problem analysis, information seeking, critical appraisal, hypothesis formulation, experimental design, data analysis and interpretation, collaboration and the ability to communicate and defend the outcomes of an investigation. This project adopted a qualitative approach to examine current teaching practice in bioscience disciplines in Australian universities. Twenty-six cases were identified where educators considered they were intentionally teaching scientific inquiry. The cases were identified from nine universities, across 11 bioscience disciplines, and were developed for all three years of undergraduate teaching. [Executive summary, ed]